(untitled) (Revista Sistemas de Producción Agroecológicos, 2014)
Tithonia diversilia is an acceptable adequate forage plant for feeding ruminants (cattle, goats, sheep and buffaloes), with good level of protein (18.9 to 28.8), high degradability in the rumen, and low fiber levels of anti-nutritional substances such as phenols and tannins, based on the above, the following research, Villavicencio, Meta, Colombia is performed. The main objective is to determine the effect of supplementation with silo (Tithonia diversifolia) in the diet of sheep for fattening, using different dry matter percentages: 0%, 0.5%, 0.75% and 1% from the live animal, assessing weight gain, feed conversion, feed efficiency and consumption of forage fed Brachiaria spp main power supply sheep. 12 weaned sheep were used with an average weight 19.4 kg the randomly distributed into 4 groups naming treatments as follows: T1: control group, unsupplemented animals; T2, T3 and T4 sheep supplemented with Tithonia diversilia silo levels: 0.5%, 0.75 and 1%, respectively. The total weight gain was lower (P<0.05) for T1 (19.68 kg) compared to T4 (20.76), with the other treatments, no differences were observed level of supplementation had the highest weight gain per day was T4 with 72.2 g/day. The intake of dry matter (DM) (g/day) was higher (P<0.05) for T4 (1149.14) compared to T1 and T2 (887.04 and 998.70). There was no significant difference (P<0.05) in T1, T2, T3, T4 treatments for variable feed conversion, feed efficiency and protein efficiency ratio. In conclusion you can use the silo Tithonia diversilia as a supplement in the diet of sheep at a rate of 1% of the dry weight relative to their body weight.